Determinants of potentially harmful traditional cord care practices among mothers in Ethiopia - Merga, Bedasa Taye; Fekadu, Gelana; Raru, Temam Beshir; Ayana, Galana Mamo; Hassen, Fila Ahmed; Bekana, Miressa; Negash, Belay; Eshetu, Bajrond; Birhanu, Abdi; Mulatu, Gutema; Balis, Bikila (Frontiers in Pediatrics, 2022)
Background Globally, newborn deaths have declined from 5 million in 1990 to 2.4 million in 2019; however, the risk of death in the first 28 days is high. Harmful umbilical cord care contributes to neonatal infection, which accounts for millions of neonatal deaths. This study assessed determinants of potentially harmful traditional cord care practices in Ethiopia using data from a nationally representative survey. Materials and methods Secondary data analyses were employed using data from the 2016 Ethiopian Demographic and Health Survey. Weighted samples of 4,402 mothers who gave birth in the last 3 years prior to the survey were included in the analysis. Binary logistic regression was fitted to identify associations of outcome variables with explanatory variable analysis, and the results were presented with an adjusted odds ratio (AOR) at a 95% confidence interval (CI), declaring statistical significance at a p-value < 0.05 in all analyses. Results About 13.70% (95% CI: 12.7%, 14.7%) of mothers practice harmful traditional umbilical cord care. Maternal age (25–34 years, AOR = 1.77, 95% CI: 1.36, 2.31, 35–49 years, AOR = 1.53, 95% CI: 1.07, 2.19), maternal education (primary: AOR = 0.54, 95% CI: 0.41, 0.70 and secondary and above: AOR = 0.61, 95% CI: 0.40, 0.94), parity (para two, AOR = 0.71, 95% CI: 0.55, 0.92), and place of delivery (home delivery, AOR = 1.96, 95% CI: 1.51, 2.56) were factors associated with potentially harmful traditional umbilical cord care practices. Conclusion Maternal educational status, parity, maternal age, and place of delivery were associated with harmful traditional cord care practices. Thus, improving mothers’ education, strengthening antenatal and postnatal care (PNC), and utilization of institutional delivery would help to reduce harmful traditional cord care practices.